IMPLEMENTASI UPAYA PENERAPAN LEAN HOSPITAL DI UNIT RAWAT JALAN RUMAH SAKIT MUTIARA HATI PAGADEN KAB.SUBANG - Kuncorosidi Kuncorosidi; Angelia Anggia Permata Norman; Rita Amelia (STIESA Press, 2022)
This study aims to analyze the application of Lean Hospital in the Outpatient unit of Mutiara Hati Hospital Pagaden Kab. Subang. This research was conducted to identify activities in the work process in the outpatient unit, and to analyze the value stream map of the outpatient unit. Based on the results of the study, it can be concluded that the results of the patient's value assessment starting from the registration process to getting the drug at the pharmacy still show that the wasting time is too long. This is due to the many obstacles that occur throughout the service process in the outpatient unit. The results identified that activities and activities during the work process of the outpatient unit were found to be wasteful, so that the ratio of value added activities (value added assessment) was less than 30%. As a form of the problem lies in humans, machine methods and environment. Proposed improvements are made by analyzing the root cause of the problem, making corrective steps by estimating the hospital's capabilities and the factors that influence it.